PENGARUH IKLAN PRODUK, KUALITAS PRODUK, DAN SERTIFIKASI HALAL TERHADAP KEPUTUSAN PEMBELIAN KOSMETIK MAKE OVER (STUDI KASUS KONSUMEN TOKO DAN+DAN WIDYA ASRI SERANG) - Agustiawati, Najya; Mukhsin, Moh; Abduh, Muhammad (At-Tawazun, Jurnal Ekonomi Syariah, 2025)
This study aims to determine the influence of advertising, product quality, and halal certification on cosmetic consumer purchase decisions. This study used a Likert scale measuring tool, using IBM SPSS Statistics 30 software. The results of regression measurement found that advertising, product quality and halal certification contributed 69.3% to cosmetic purchase decisions. The results of the study partially (t-test) stated that the advertising variable had a tcount>ttable (16,617>1,991) and a significant value smaller than the probability value (0.000 < 0.05), this means that the advertisement had a significant positive effect on the decision to purchase cosmetics, the product quality variable had a tcount>ttable (3,551>1,991) and a significant value smaller than the probability value (0.001<0.05) this shows that the product quality has a positive effect Significant to the purchase decision, the halal certification variable has a tally of tcount<ttable (158>1,991) and a significant value greater than the probability value (875>0.05) this shows that halal certification does not have a significant positive effect on cosmetics purchase decisions. The results of the simultaneous study (f-test) have a tcount>ftable value (458,576>2.72) and a probability value (sig) of 0.000 so that the value of sig < 0.05 (0.000 < 0.05) can be concluded that advertising, product quality, and halal certification have a positive and significant effect on the decision to purchase makeover cosmetics at the Dan+Dan Widya Asri Serang store.